Internal migration in the time of Covid: Who moves out of the inner city of Stockholm and where do they go? - Vogiazides, Louisa; Kawalerowicz, Juta (Population space and place, 2023)
After the outbreak of the COVID‐19 pandemic, the media abounded with stories of people ‘fleeing city‐centres’ and ‘finding refuge in the countryside’. A recurrent argument is that the shift towards remote work has prompted individuals to reconsider their living situation and envisage the possibility of relocating further away from their workplace. The aim of this study is to examine the patterns of out‐migration from the Stockholm inner city during the COVID‐19 pandemic, as well as the characteristics of out‐migrants. We use Swedish register data to compare the trends for the first year of the COVID‐19 pandemic (2020) and the 5 years preceding it (2015–2019). Our study shows that, similar to other large cities across the world, individuals moved out of the inner city of Stockholm to a higher degree in 2020 than during the years preceding the pandemic. The majority of movers relocated to the Stockholm suburbs, which experienced a substantial increase in inflows from the Stockholm inner city. Yet a number of smaller municipalities, including traditional tourist destinations, also received more residents from the Stockholm inner city in 2020. Although it remains to be seen whether the increase in out‐migration from the Stockholm inner city observed in 2020 will be a long‐term trend, the paper discusses the policy implications of inner city out‐migration, from the perspective of both the sending and the receiving locations.